The potential biomedical platforms based on the functionalized Gd@C82 nanomaterials. Issue 1 (23rd March 2020) - Li, Xue; Wang, Chunru
Abstract: Gadolinium metallofullerene (Gd@C82 ), a novel star carbonaceous material, has allured considerable attention due to its attractive properties. Increasing evidence exhibits that functionalized Gd@C82 nanomaterials have great potential in various biomedical applications. Except for the earliest bioapplication as the next‐generation of magnetic resonance imaging contrast agent, Gd@C82 nanomaterials perform excellent anti‐cancer activities. Functionalized Gd@C82 nanomaterials could inhibit tumor growth by suppressing tumor angiogenesis, cutting off the existing tumor vasculature under radiofrequency irradiation or modulating immune cells. In addition, Gd@C82 nanomaterials could be adjuvant agents to lower the toxicity of chemotherapeutic drugs and alleviate drug resistance. In particular, Gd@C82 nanomaterials are demonstrated to regulate glucose and lipid metabolism, presenting superior anti‐type 2 diabetes mellitus effects. With no detectable toxicity and pleiotropic biological effects, Gd@C82 nanomaterials could be promising biomedical platforms in the future. Abstract : Functionalized Gd@C82 nanomaterials have been used in various biomedical fields, such as cancer diagnosis and treatment, glucose and lipid modulation, etc. With no detectable toxicity and pleiotropic biological effects, Gd@C82 nanomaterials could be promising biomedical platforms in clinical usein the future.